To find the intersection point of the two equations \( y = 5x + 10 \) and \( y = -2x + 3 \), we can set them equal to each other:
\[ 5x + 10 = -2x + 3 \]
Next, we can solve for \( x \):
-
Add \( 2x \) to both sides: \[ 5x + 2x + 10 = 3 \] \[ 7x + 10 = 3 \]
-
Subtract \( 10 \) from both sides: \[ 7x = 3 - 10 \] \[ 7x = -7 \]
-
Divide by \( 7 \): \[ x = -1 \]
Now that we have \( x = -1 \), we can substitute this value back into either equation to find \( y \). Let's use the second equation:
\[ y = -2(-1) + 3 \] \[ y = 2 + 3 = 5 \]
Thus, the solution to the system of equations is \( (-1, 5) \).
Based on the options you've provided, the correct answer is: (−1, 5).